Populasi, Sampel, Parameter, Statistik, Data, Datum, Data Mentah, Variabel Kuantitatif dan Kualitatif Variabel, Variabel Kontinu dan Variabel Diskrit - Suciani, Anggun; Aqila, Nazwa; Maya, Windi Dwi (CV. Rayyan Dwi Bharata, 2025)
This article discusses the basic concepts in statistics that are an important foundation for both quantitative and qualitative research. The main focus includes the understanding and relationship between population, sample, parameter, and statistics as basic elements in the process of scientific conclusion making. In addition, this article explains the difference between data and datum, and the importance of understanding raw data before processing it. This article also describes the classification of variables into quantitative and qualitative variables, and further distinguishes between continuous and discrete variables. Understanding these terms is essential for researchers to design, process, and analyze data properly in order to produce valid and reliable information. This article aims to provide a comprehensive understanding for readers who are new to statistics or who want to strengthen their basic knowledge.